Estimation of Net Social Benefits from Outdoor Recreation - Burt, Oscar R.; Brewer, Durward (Econometrica, 1971)
[An economic framework is presented for measurement of the net social benefits that can be attributed to development of a new outdoor recreation site, taking into consideration the influence that existing recreation developments have on the demand for services from the newly developed site. Methods are given for statistically estimating the empirical measures needed to apply the model, and an application is made to water-oriented outdoor recreation in Missouri. Results of the application suggest that investments in outdoor recreation can be evaluated under an objective economic decision criterion.]